2014
DOI: 10.1158/1055-9965.epi-13-0744
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a Biospecimen Collection Seminar on Willingness to Donate Biospecimens among Chinese Americans: Results from a Randomized, Controlled Community-Based Trial

Abstract: Background Biospecimen collection from diverse populations can advance cancer disparities research, but is currently underrepresented. Methods We partnered with a community-based clinic serving Cantonese-speaking Chinese Americans to develop and revise an educational seminar on biospecimen collection. Through a randomized controlled trial (n = 395), the intervention seminar was compared with a control seminar (cancer prevention) on change in willingness to donate biospecimens. Results At baseline, many wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
38
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(42 citation statements)
references
References 21 publications
4
38
0
Order By: Relevance
“…(Durant et al, 2007; Hagiwara et al, 2014; Rodriguez, Torres, & Erwin, 2013; Wendler et al, 2005) After the seminars, however, the percentage of health care providers who intended to always or often speak to patients was 49.5%, a significant increase. Other studies have found similar results after training (Dang et al, 2014; Gao et al, 2014; Tong et al, 2014) however, there is a dearth of studies examining the actual practice of providers after training in providing content about biospecimens.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…(Durant et al, 2007; Hagiwara et al, 2014; Rodriguez, Torres, & Erwin, 2013; Wendler et al, 2005) After the seminars, however, the percentage of health care providers who intended to always or often speak to patients was 49.5%, a significant increase. Other studies have found similar results after training (Dang et al, 2014; Gao et al, 2014; Tong et al, 2014) however, there is a dearth of studies examining the actual practice of providers after training in providing content about biospecimens.…”
Section: Discussionmentioning
confidence: 86%
“…Previous studies also have demonstrated an increase in knowledge and intention to donate among underserved groups trained in the importance of biospecimen donation. (Gao et al, 2014; Tong et al, 2014)…”
Section: Discussionmentioning
confidence: 99%
“…As shown in prior studies, being asked to participate is essential, and the convenience of participating at the community level is important, rather than having to seek out the opportunity at a research center (Hagiwara et al 2014;Kiviniemi et al 2013). Regardless of information transfer method (i.e., open event or structured group education), transparency in explaining the process and what is being asked of the participant, as well as providing examples of research that are relevant to the community or population of interest, is critical in engaging diverse disease-free (i.e., without a cancer diagnosis) adults in biospecimen donation Tong et al 2014). Lastly, our data also included information from participants on knowing a family member or friend with cancer and how that factored into their willingness to donate to the DBBR.…”
Section: Limitations/strengthsmentioning
confidence: 99%
“…However, community outreach that includes education on biospecimen research practices and efforts has resulted in a high level of interest in biospecimen donation Dash et al 2014;Hagiwara et al 2014;Kiviniemi et al 2013;Luque et al 2012;Rodriguez et al 2013;Tong et al 2014). A commonly cited barrier to biomedical research participation among African Americans is Bmedical mistrust,^but findings from Hagiwara et al (2014) and Dash et al (2014) both support that this is not the most reported barrier for biospecimen donation among this population.…”
Section: Introductionmentioning
confidence: 99%
“…Older Chinese participants have also been found to be more willing to donate to research if it benefits future generations. 21 These findings also suggest that participants who have lived in the US longer, had a higher income, or who had a regular doctor to visit were more willing to donate blood for research purposes. This suggests that people who have lived in the US longer or who have a regular doctor may have more positive attitudes toward medical research and the US medical care system, which increases their willingness to donate blood for research.…”
Section: Discussionmentioning
confidence: 90%